The Relationship between Nutritional Status and The Quality of Life for Elderly in RW 3 area of Pasar Minggu, Jakarta, Indonesia - Lubis, Misri Yanty (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Background. Person’s physical abilities will decrease when elderly. The definition of elderly is someone who has reached the age of more than 60 years. Decreased physical ability can lead to reduced nutritional status which has an impact on decreasing quality of life. The aim of this study was to determine the relationship between nutritional status and the quality of life for elderly in RW 3 area of Pasar Minggu. Methods. This study used a quantitative correlation design with a cross sectional approach. The population of this study is the elderly in the RW 3 area of Pasar Minggu. Data was collected from 187 respondents through a questionnaire. The data obtained were analyzed by SPSS. Result. Study showed malnutrition 45%, normal 35%, obesity 20% and good quality of life 35%, poor quality of life 65%. Test result p value, 0.002